The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1186/s12933-023-01814-7
|View full text |Cite
|
Sign up to set email alerts
|

SGLT2-inhibitors effects on the coronary fibrous cap thickness and MACEs in diabetic patients with inducible myocardial ischemia and multi vessels non-obstructive coronary artery stenosis

Abstract: Background Sodium–glucose transporter 2 inhibitors (SGLT2-I) could modulate atherosclerotic plaque progression, via down-regulation of inflammatory burden, and lead to reduction of major adverse cardiovascular events (MACEs) in type 2 diabetes mellitus (T2DM) patients with ischemic heart disease (IHD). T2DM patients with multivessel non-obstructive coronary stenosis (Mv-NOCS) have over-inflammation and over-lipids’ plaque accumulation. This could reduce fibrous cap thickness (FCT), favoring pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 33 publications
(95 reference statements)
0
19
0
Order By: Relevance
“…Eighteen studies examined the effects of GLP-1 RA [ 11 – 13 , 16 31 ], and eleven examined the effects of SGLT2i on IMT [ 32 42 ]. Studies that did not provide IMT results [ 43 – 49 ], duplicate data [ 50 – 56 ], combination therapies without apparent GLP-1 RA effects [ 57 ], or assessed IMT of arteries other than the carotid artery were excluded [ 58 60 ]. The study selection process is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Eighteen studies examined the effects of GLP-1 RA [ 11 – 13 , 16 31 ], and eleven examined the effects of SGLT2i on IMT [ 32 42 ]. Studies that did not provide IMT results [ 43 – 49 ], duplicate data [ 50 – 56 ], combination therapies without apparent GLP-1 RA effects [ 57 ], or assessed IMT of arteries other than the carotid artery were excluded [ 58 60 ]. The study selection process is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…The principle cytokines are mainly IL8 and TNFα with Hs-CRP (Hypersensitive C-Reactive Protein) for AMI 10 11 , TNFα, Hs-CRP, IL6 with STEMI patients 12 , IL-1ß for coronary endothelial dysfunction in CAD (Coronary Artery Disease) patients 13 , IL6, IL8, and TNFα for patients with severe stenosis in a saphenous vein 14 , TNFα for restenosis patients after coronary angiography 15 , IL-1ß, IL6 and TNFα for AMI patients with signi cant stenosis of the ramus interventricularis anterior 16 . T2DM Mv-NOCS patients with SGLT2 inhibitor users showed reduced BMI, and in ammation than non-users with lower levels of NLRP3 in ammasome formation and IL-1ß 17 . Adiponectin that is exclusively secreted from adipose tissue and in ammatory cytokines including TNFα, PAI-1 (Plasminogen Activator Inhibitor type 1), IL-6, leptin, and resistin favorably modulate the endothelial in ammatory responses to vascular injury 18 and linked to restenosis and Acute Coronary symptoms after PCI 19 .…”
Section: Introductionmentioning
confidence: 86%
“…Indeed, more evidence is emerging that SGLT2 inhibitors may have ameliorative effects on glucose homeostasis and advantageous pleiotropic glucose-independent effects on coronary plaque development. A recent study showed that DM patients with multivessel non-obstructive CAD treated with SGLT2 inhibitors had significantly higher values of OCT-detected fibrous cap thickness, fewer lipid deposits (measured as the lipid arc) and less macrophage infiltration than DM patients not treated with SGLT2 inhibitors [ 78 ]. In addition, a lower incidence of major adverse cardiovascular events was observed in this patient group [ 78 ].…”
Section: Medical Treatment Strategiesmentioning
confidence: 99%
“…A recent study showed that DM patients with multivessel non-obstructive CAD treated with SGLT2 inhibitors had significantly higher values of OCT-detected fibrous cap thickness, fewer lipid deposits (measured as the lipid arc) and less macrophage infiltration than DM patients not treated with SGLT2 inhibitors [ 78 ]. In addition, a lower incidence of major adverse cardiovascular events was observed in this patient group [ 78 ]. Furthermore, in other studies with DM patients treated by PCI after MI, SGLT2 inhibitors were associated with a reduction in both safety outcomes and in-stent restenosis-related events [ 79 , 80 ].…”
Section: Medical Treatment Strategiesmentioning
confidence: 99%